Relasi Islam Dan Demokrasi Dalam Perspektif Islam : Kajian Teoritis Dari Sudut Pandangan Tokoh - Moh. Syafi’i; Muhammad Najib (Pascasarjana Universitas Qomaruddin, 2024)
The plurality of Indonesian society cannot be separated from the state system that will be used. With a democratic system based on Pancasila, it will greatly minimize friction between tribes and religions. However, the challenge to democracy in Indonesia is the groups who are against democracy. The approach used in this study is a qualitative approach. This research is in the form of library research from the study of the character's thinking. The researcher uses Content Analysis technique by recording factual information and includes a detailed and accurate description of various dimensions related to all aspects studied. So, in this study, the researcher described the results by taking materials that were appropriate to the problem, then the data were analyzed, combined, and concluded. Islam and Democracy cannot be separated from one another, because the values ​​of Islamic teachings are contained in the foundation of the Indonesian state, namely Pancasila. As for the efforts that can be made, of course there must be prevention efforts from the government and from among students and students. The government's efforts that can be done, of course, must be combing and mapping which groups are included in the fundamentalists with mutual consolidation on the part of the government and the fundamentalists. As for the efforts of the students, of course, to educate the general public about the dangers of anarchism and textualism to democracy in Indonesian society. Likewise, santri, they must be able to preach in a polite manner and provide education about the values ​​of Islamic teachings.